2008
DOI: 10.1177/1553350608317354
|View full text |Cite
|
Sign up to set email alerts
|

Initial Laparoscopic Access Using an Optical Trocar Without Pneumoperitoneum Is Safe and Effective in the Morbidly Obese

Abstract: Obtaining access to the peritoneal cavity in laparoscopic surgery is more difficult in morbidly obese people. The aim of this study was to examine the safety and efficacy of accessing the peritoneal cavity using an optical, bladeless trocar without previous pneumoperitoneum in morbidly obese patients. The patients' characteristics and outcomes with consecutive and preferential use of an optical, bladeless, first trocar insertion without previous pneumoperitoneum in morbidly obese patients (body mass index > 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…These include a left upper quadrant approach for the initial Veress needle placement [23], especially when mid-abdominal adhesions were anticipated, and/or use of a 5 mm diameter, 150-mm-long optical bladeless trocar guided by a separate laparoscopic camera for placement of the initial trocar into the umbilicus or left upper quadrant. The latter technique for obese patients is commonly used by laparoscopic gastric bypass surgeons [24]. We also found that laparoscopic lysis of adhesions can be more easily done with a lightweight handheld camera using a separate bank of instruments.…”
Section: Discussionmentioning
confidence: 95%
“…These include a left upper quadrant approach for the initial Veress needle placement [23], especially when mid-abdominal adhesions were anticipated, and/or use of a 5 mm diameter, 150-mm-long optical bladeless trocar guided by a separate laparoscopic camera for placement of the initial trocar into the umbilicus or left upper quadrant. The latter technique for obese patients is commonly used by laparoscopic gastric bypass surgeons [24]. We also found that laparoscopic lysis of adhesions can be more easily done with a lightweight handheld camera using a separate bank of instruments.…”
Section: Discussionmentioning
confidence: 95%
“…Incidental injuries might occur easier despite the visual control obtained by the camera inside the port. Additionally, while using optical trocars for laparoscopic access has been reported in great numbers in the upper abdomen1719, only few reports can be found about their use in the lower abdomen and safety in that anatomical region might be reduced 19. Despite this uncertainty, a Foley catheter should be positioned during any supra-pubic access case to minimize the risks of any inadvertent bladder injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Rabl et al ont montré dans une série rétrospective de 208 patients obèses (IMC > 35 kg/m 2 ) que l'introduction du premier trocart sans lame avec système optique intégré sans pneumopéritoine préalable était sûre et efficace. Il n'existait pas de complications majeures [11]. Rosenthal et al ont montré dans une étude prospective portant sur 844 patients obèses (IMC moyen de 53,2 kg/m 2 ) que l'utilisation d'un trocart de 12 mm sans lame et avec système optique intégré sans pneumopéritoine préalable était sûre et permettait la reconnaissance et la réparation d'une lésion éventuelle immédiate.…”
Section: Obésitéunclassified
“…Il n'existe pas de contre-indication de mise en place du premier trocart avec système optique intégré sans pneumopéritoine au préalable chez le patient obèse [9][10][11][12]14]. La création du pneumopéritoine selon la technique fermée par aguille de Veress en hypochondre gauche est sûre chez l'obèse morbide [13].…”
Section: Obésitéunclassified